"I'm No Superman": Understanding Diabetic Men, Masculinity, and Cardiac Rehabilitation. (December 2015) - Dale, Craig M.; Angus, Jan E.; Seto Nielsen, Lisa; Kramer-Kile, Marnie; Pritlove, Cheryl; Lapum, Jennifer; Price, Jennifer; Marzolini, Susan; Abramson, Beth; Oh, Paul; Clark, Alex
Exercise-based cardiac rehabilitation (CR) programs help patients with coronary heart disease (CHD) reduce their risk of recurrent cardiac illness, disability, and death. However, men with CHD and Type 2 diabetes mellitus (T2DM) demonstrate lower attendance and completion of CR despite having a poor prognosis. Drawing on gender and masculinity theory, we report on a qualitative study of 16 Canadian diabetic men recently enrolled in CR. Major findings reflect two discursive positions men assumed to regain a sense of competency lost in illness: (a) working with the experts, or (b) rejection of biomedical knowledge. These positions underscore the varied and sometimes contradictory responses of seriously ill men to health guidance. Findings emphasize the priority given to the rehabilitation of a positive masculine identity. The analysis argues that gender, age, and employment status are powerful mechanisms of variable CR participation.